The Effect of Word Wall Application on the Interest in Learning Arabic Language of Students in Class VIII MTS.N 3 Kab.Gorontalo - F. Kadullah, Nursiyah; Abdullah, Abdullah; Mooduto, Dzulkifli (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The low interest in learning students is caused by the lack of use of media which can make the learning atmosphere more enjoyable. The word wall application is a website that has various types of interactive quiz games. The word wall application is a website that has various types of interactive quiz games. The purpose of the study was to find the effect of using word wall applications on learning outcomes. This type of research is experimental research and uses a Quasi-Experimental research design, which can compare with the situation before and after treatment. The results of the research that the author did are, that the word wall application has an influence on student learning interest in Arabic subjects, Based on the results of the analysis that there is an influence of word wall applications on student learning interest in Arabic subjects, this can be seen in the Independent Sample Test test to obtain a significance value (2-tailed) < 0.05, then there is a significant influence on the experimental class. It can be concluded that H1 is accepted and H0 is rejected.